Promotion of intellect through knowledge transfer - Janon, Nazariah Shar'ie (IIUM Press, International Islamic University Malaysia, 2020)
This chapter attempts to explain a knowledge transfer project from IIUM to people in the community. The project transfer a psychological knowledge and skills on typical and non-typical children to preschool assistant teachers in Selangor. The knowledge transfer project does not only enhance their knowledge in interacting and dealing with typical and non-typical children but also providing them platform to continue seeking knowledge that is one way in preserving their intellect and sustaining high job quality.